A Project Report on Brain Machine Interface on Robots - AAREKH PRAKASH, RITURAJ BHUSHAN, SONAL ROY and SUPRIYA DEKA (2014)
INTERNAL GUIDE: MRS KALA H S, MVJCE
Keywords: Brain Machine Interface on Robots